Ability-Enhancing Practices and Organisational Performance: Does Justice Perception Moderate the Relationship in The Context of Police Force in Nigeria? - Idowu Owoeye; David Kiiru; Jedidah Muli (European Scientific Journal, ESJ, 2020)
The knowledge, skills, and abilities constituting employee characteristics are often described as the capacity needed by a firm to attain competitive advantage which in turn occasions performance outcomes at various firm’s levels. While evidence of significant and insignificant relationships between ability-enhancing practices and performance outcomes at firm’s levels has been registered across organisational contexts in human resource management literature, such evidence remains limited and anecdotal in the context of criminal justice system in Nigeria. Using a survey data from 321 police officers, this study investigated the interactional effect of justice perception on the relationship between ability-enhancing practices and performance of police force in Nigeria. The study adopted both descriptive and explanatory designs, and the study instruments were adapted. The validity and reliability of the study instruments were determined via Principal Component Analysis, and thereafter data collected were analysed employing both descriptive and inferential statistical methods with the aid of analytical tool of Statistical Package for Social Sciences. The moderating effect of justice perception was established using PROCESS macro and the results were interpreted using Baron and Kenny’s (1986) approach for determining mediation effect. The results of the analysis revealed that the performance of police force in Nigeria was predicted by composite construct of ability enhancing practices, and the relationship was completely moderated by justice perception. The results also revealed significant effects of rigorous recruitment and selection, and coaching on performance of police force, however, insignificant effects of job rotation and mentoring practices were found with performance of police force in Nigeria. The study contributes to the body of empirical knowledge that individual’s perception of fairness of the implemented organisational systems to enhance employee knowledge, skills, and abilities is vital to the attainment of favourable performance outcomes. The institution of Criminal Justice System can leverage on the findings of this study to improve human capital development so as to attain desired performance outcomes.